2012
DOI: 10.1080/03601234.2012.632249
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of nicosulfuron by the bacteriumSerratia marcescensN80

Abstract: By enrichment culturing of the sludge collected from the industrial wastewater treatment pond, we isolated a highly efficient nicosulfuron degrading bacterium Serratia marcescens N80. In liquid medium, Serratia marcescens N80 grows using nicosulfuron as the sole nitrogen source, and the optimal temperature, pH values, and inoculation for degradation are 30-35°C, 6.0-7.0, and 3.0% (v/v), respectively. With the initial concentration of 10 mg L⁻¹, the degradation rate is 93.6% in 96 hours; as the initial concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…These results suggest that the percent removal of herbicide decreased with increasing amount of strain ZWS16. Similar results have been reported for degradation of sulfonylurea herbicides Zhang et al 2012). …”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…These results suggest that the percent removal of herbicide decreased with increasing amount of strain ZWS16. Similar results have been reported for degradation of sulfonylurea herbicides Zhang et al 2012). …”
Section: Resultssupporting
confidence: 78%
“…The optimal temperatures for degradation of nicosulfuron by S. marcescens N80 were 30-35°C, and the percent degradation decreased when the temperature was lower than 20-30°C or higher than 40°C (Zhang et al 2012). The percent degradation of pyrazosulfuron-ethyl at 28°C was faster than that at 20 and 37°C by Pseudomonas sp., whereas the highest percent degradation for Bacillus sp.…”
Section: Resultsmentioning
confidence: 98%
“…For instance, strain BW30 was capable of converting glucose (or other carbon compounds in soil) into short-chain fatty acids, including oxalic and lactic acids. These short-chain fatty acids then attacked the sulfonylurea bridge and finally resulted in the breakdown of TBM molecules 37 . In our study, glucose metabolism was essential to nicosulfuron degradation by Penicillium oxalicum YC-WM1.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, high concentrations of dissolved organic C (Arts et al, 2000; mean concentrations of 11.9 to 17.6 mg L −1 ; Supplemental Table S1) and ice cover in winter, both of which are characteristic of prairie surface waters, would have reduced photodegradation in the current study through attenuation of ultraviolet light. Microbial degradation of sulfosulfuron has been reported in soil (Brar et al, 2006), and rimsulfuron (Zhang et al, 2012) and nicosulfuron (Song et al, 2013; Zhang et al, 2012) have been shown to be microbially degraded in aqueous media. Thus, biotic degradation of these herbicides may have contributed to their dissipation in the water column of the dugouts in the current study (Fig.…”
Section: Resultsmentioning
confidence: 99%